Load sustained rig for bond durability study - Abu Hassan, Shukur; Ismail, Yob Saed; Mohd. Sam, Abd. Rahman (Faculty of Mechanical Engineering, 2009)
This paper describes the development of a special-built experimental rig used for bond durability study of composites specimen under combination of sustainable mechanical load and weathering effects. The specimen under study was Carbon Fibre-Reinforced Plastic (CFRP) plates bonded with special structural epoxy adhesive to a concrete prism. The fully mechanical rig was designed to create and sustain pull-push load configuration to the specimen. From setting-up process, laboratory monitoring works and CFRP plate strain data, it shows that the rig performed well without any maintenance throughout the period